2011
DOI: 10.1597/09-217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence at Birth of Cleft Lip with or without Cleft Palate: Data from the International Perinatal Database of Typical Oral Clefts (IPDTOC)

Abstract: As part of a collaborative project on the epidemiology of craniofacial anomalies, funded by the National Institutes for Dental and Craniofacial Research and channeled through the Human Genetics Programme of the World Health Organization, the International Perinatal Database of Typical Orofacial Clefts (IPDTOC) was established in 2003. IPDTOC is collecting case-by-case information on cleft lip with or without cleft palate and on cleft palate alone from birth defects registries contributing to at least one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
74
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(103 citation statements)
references
References 31 publications
10
74
1
4
Order By: Relevance
“…Worldwide, the birth prevalence is 1/700 live births [15]. Prevalence is highest in Asians (1/500), intermediate in Caucasians (1/1,000), and lowest in African populations (1/2,500) [8,15-18]. Clefts of the lip have a 2:1 male to female ratio, while clefts of the palate have a 1:2 male to female ratio [15].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the birth prevalence is 1/700 live births [15]. Prevalence is highest in Asians (1/500), intermediate in Caucasians (1/1,000), and lowest in African populations (1/2,500) [8,15-18]. Clefts of the lip have a 2:1 male to female ratio, while clefts of the palate have a 1:2 male to female ratio [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cleft lip and/or palate (CL/P) is a surgical condition of multifactorial etiology that disproportionately affects the poorest populations throughout the world. The prevalence of CL/P varies by region and global estimates range from 1 in 700 to 1 in 1000 live births worldwide [8,9]. While infant mortality is only modestly affected by CL/P in high-income settings, studies have demonstrated high infant mortality rates in even isolated forms of this condition in Latin America, as well as up to a seven-fold increase in risk of neonatal death in China [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Perinatal Database of Typical Orofacial Clefts (IPDTOC) working group, the proportion of bilateral cases is 10.3% for cleft lip without palate (CL) and 30.2% for cleft lip with palate (CLP). Amongst unilateral cases, 36.9% of CL and 41.1% of CLP occur on the right side, suggesting that unilateral cases of CL/P occur more frequently on the left [7].…”
Section: Lateralitymentioning
confidence: 98%